Gluten‐free diet increases beta‐cell volume and improves glucose tolerance in an animal model of type 2 diabetes. Issue 7 (21st April 2016) - Haupt‐Jorgensen, Martin; Buschard, Karsten; Hansen, Axel K.; Josefsen, Knud; Antvorskov, Julie Christine
Abstract: Background: Gluten‐free (GF) diet alleviates type 1 diabetes in animal models and possibly in humans. We recently showed that fatty acid‐induced insulin secretion is enhanced by enzymatically digested gluten (gliadin) stimulation in INS‐1E insulinoma cells. We therefore hypothesized that GF diet would induce beta‐cell rest and ameliorate type 2 diabetes. Methods: C57BL/6JBomTac (B6) mice were fed a high‐fat (HF), gluten‐free high‐fat (GF–HF), standard (STD) or gluten‐free (GF) diet for 42 weeks. Results: Short‐term (6–24 weeks) GF–HF versus HF feeding impaired glucose tolerance and increased fasting glucose. Long‐term (36–42 weeks) GF–HF versus HF feeding improved glucose tolerance and decreased fasting leptin. Mice fed a GF–HF versus HF diet for 42 weeks showed higher volumes of beta cells, islets and pancreas. The beta‐cell volume correlated with the islet‐ and pancreas volume as well as body weight. GF–HF versus HF diet did not influence toll‐like receptor 4 ( Tlr4 ), interleukin 1 ( IL‐1 ), interleukin 6 ( IL‐6 ) or tumour necrosis factor‐alpha ( TNF‐alpha ) mRNA expression in intestine. STD versus GF feeding did not affect any parameter studied. Conclusions: Long‐term feeding with GF–HF versus HF increases beta‐cell volume and improves glucose tolerance in B6 mice. The mechanism may include beta‐cell rest, but is unlikely to include TLR4 and proinflammatory cytokines in the intestine. Beta‐cell volume correlates with pancreas volume and body weight, indicating that insulin secretion capacity controls pancreas volume. Thus, long‐term GF diets may be beneficial for obese type 2 diabetes patients and trials should be performed. Copyright © 2016 John Wiley & Sons, Ltd.